The Emerging Link Between the Complement Cascade and Purinergic Signaling in Stress Hematopoiesis - Ratajczak, Mariusz Z.; Adamiak, Mateusz; Kucia, Magda; Tse, William; Ratajczak, Janina; Wiktor-Jedrzejczak, Wieslaw (Frontiers in Immunology, 2018)
Innate immunity plays an important role in orchestrating the immune response, and the complement cascade (ComC) is a major component of this ancient defense system, which is activated by the classical-, alternative-, or mannan-binding lectin (MBL) pathways. However, the MBL-dependent ComC activation pathway has been somewhat underappreciated for many years, recent evidence indicates that it plays a crucial role in regulating the trafficking of hematopoietic stem/progenitor cells (HSPCs) by promoting their egress from bone marrow (BM) into peripheral blood (PB). This process is initiated by the release of danger-associated molecular patterns (DAMPs) from BM cells, including the most abundant member of this family, ATP. This nucleotide is well known as a ubiquitous intracellular molecular energy source, but when secreted becomes an important extracellular nucleotide (EXN) signaling molecule and mediator of purinergic signaling. What is important for the topic of this review, ATP released from BM cells is recognized as a DAMP by MBL, and the MBL-dependent pathway of ComC activation induces a state of “sterile inflammation” in the BM microenvironment. This activation of the ComC by MBL leads to the release of several potent mediators, including the anaphylatoxins C5a and desArgC5a, which are crucial for egress of HSPCs into the circulation. In parallel, as a ligand for purinergic receptors, ATP affects mobilization of HSPCs by activating other pro-mobilizing pathways. This emerging link between the release of ATP, which on the one hand is an activator of the MBL pathway of the ComC, and on the other hand is a purinergic signaling molecule, will be discussed in this review. This mechanism plays an important role in triggering defense mechanisms in response to tissue/organ injury but may also have a negative impact by triggering autoimmune disorders, aging of HSPCs, induction of myelodysplasia, and graft-versus-host disease (GvHD) after transplantation of histoincompatible hematopoietic cells.